2018
DOI: 10.1086/697567
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Primary Care and Social Work: A Systematic Review

Abstract: Behavioral and physical health services are increasingly being integrated, with care provided by interprofessional teams of physicians, nurses, social workers, and other professionals. The objective of this study was to describe the functions of social workers on interprofessional teams in primary care and to assess the impact of interprofessional teams that include social workers in integrated care settings. Method: We undertook a systematic review of randomized controlled trials (RCTs) of routine vs. integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 104 publications
2
67
0
Order By: Relevance
“…This study shows the beneficiary participation of MSW in the multidisciplinary care of patients with burn injuries. With more evidence suggesting improved outcome for patients, families and communities in integrated patient care and the added value of social workers on such healthcare teams (19,22,24), burn surgeons in similar settings are advised to get more participatory involvement of the MSW in their practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows the beneficiary participation of MSW in the multidisciplinary care of patients with burn injuries. With more evidence suggesting improved outcome for patients, families and communities in integrated patient care and the added value of social workers on such healthcare teams (19,22,24), burn surgeons in similar settings are advised to get more participatory involvement of the MSW in their practice.…”
Section: Resultsmentioning
confidence: 99%
“…The MSW obtained financial support for the patients, mainly by engaging the patient's home community, ultimately lowering the cost of care. Fraser et al in their review of studies reported ten studies where social workers engaged community resources on behalf of patients and their families, and noted that seven of those studies demonstrated findings favoring integrated care (19). Without financial support, access to healthcare would have been impossible for the patients, thereby increasing their potential morbidity and mortality and escalating the attendant cost of care.…”
Section: Discussionmentioning
confidence: 99%
“…We coded a number of methodological and general IPC variables for description of the studies, including the type of design (correlational; cross-sectional; longitudinal; experimental; other); type of study (quantitative, qualitative, combination, or study is explicitly designed as a mixed methods study); sample size; study focuses on child, parent, practitioner and/or management; and the focus on the interaction between these stakeholders (e.g., child-practitioner; parent-practitioner; practitioner-practitioner; management-practitioner); type of measure(s) (interview, survey, focus group, observation, other); study participants: professionals, children and/or parents [45]. Further, we coded the sector (childcare, school, social work, youth care, other) and type of care (primary care in a community service or special care for a specific target group), and the roles of IPC [4,10]: supportive and nurturing; health education and promotion; resources and referral; assessment and monitoring.…”
Section: Coding Of Studiesmentioning
confidence: 99%
“…A nurse, social worker, or medical assistant may be hired as a patient navigator, case manager, care manager, or panel manager, and their responsibilities might be identical or distinct. For example, social workers, professionals whose roles have typically been narrowly defined in health care settings, have recently become more involved partners in the ranks of health care workers; the responsibilities of these social workers are likely to bridge clinical and community settings [14]. A social worker working in a care management position might provide behavioral health treatment in a hospital, while also coordinating a necessary inspection of the rental home of a patient with chronic asthma to assess for unhealthy levels of asthma-causing mold.…”
Section: Boundary Spanning Rolesmentioning
confidence: 99%
“…A social worker working in a care management position might provide behavioral health treatment in a hospital, while also coordinating a necessary inspection of the rental home of a patient with chronic asthma to assess for unhealthy levels of asthma-causing mold. These boundary spanning roles and positions are new, and the functions, tasks, and payment mechanisms associated with these positions are not yet well-defined [14].…”
Section: Boundary Spanning Rolesmentioning
confidence: 99%